Programmable cam mechanisms - Wong, Poi Siong. (2008)
Metal forming press is one of the most commonly used manufacturing machines. A small improvement may add to significant corporate gain. The metal forming presses can be divided into two main categories: mechanical presses and hydraulic presses. The former is fast and energy efficient; the latter are flexible and accurate, but expensive to build and to operate. In this project, the author making use of the new mechanical press design proposed by R. Du and W. Z Guo and investigates how well it performs. This new design is basically using a new type of mechanism called hybrid mechanism to perform metal forming operation. Some of the designs of manufacturing machines have been incorporated with this new mechanism.